Role of EU in Sustainable Fashion Development - Geršlová, Barbora; Křečková Kroupová, Zuzana, 1972-; Power, Jess; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This research aims to analyse the current state of fashion and assess its negative impact on environmental and social issues, while investigating the role of EU in the transformation of the fashion industry into a sustainable business. It attempts to quantify the negative effects and to suggest improvements from EU perspective in order to avoid reaching the environmental critical point caused by the fashion industry.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses